2019
DOI: 10.21776/ub.apmba.2019.008.02.3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Earnings Quality on Financial Performance in Indonesia : is the State-Owned Bank better than Private Bank?

Abstract: The primary objective of this study is to analyze the effect of earnings quality on financial performance of banks in Indonesia. The study also aims to compare in which type of banks the independent variable has more influence on the dependent variable, whether state-owned or private banking. Indicators for earnings quality are discretionary accruals and earnings persistence while measurements for financial performance are return on assets, return on equity, rate return on loans and total asset turn over. Eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
0
6
1
2
Order By: Relevance
“…This finding is important information for companies to encourage in making quality financial reports. This result is not in line with several previous studies that found the effect of earnings quality on financial performance (Machdar & Murwaningsari, 2017;Utami et al, 2019).…”
Section: Regression Resultscontrasting
confidence: 96%
See 2 more Smart Citations
“…This finding is important information for companies to encourage in making quality financial reports. This result is not in line with several previous studies that found the effect of earnings quality on financial performance (Machdar & Murwaningsari, 2017;Utami et al, 2019).…”
Section: Regression Resultscontrasting
confidence: 96%
“…Then the quality of financial information can improve the company's image so that it helps in business activities that can improve the company's financial performance. Some previous studies found a positive effect on earnings quality on financial performance (Machdar & Murwaningsari, 2017;Utami, Nuzula, & Damayanti, 2019) but the opposite was found in other studies where earnings quality had a negative influence on financial performance (Ma & Ma, 2017;Sanjaya & Deviesa, 2017).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Sumber dana yang digunakan akan memiliki biaya tetap, karena itu diharapkan dapat memperbesar keuntungan, yang juga akan meningkatkan keuntungan bagi pemegang saham, dimana akan terlihat dari perubahan earning per share. Penelitian ini sejalan dengan Dewi & Devie (2017) dan Utami et al (2019) mengutarakan bahwa kualitas laba signifikan berpengaruh terhadap kinerja keuangan, juga senada dengan pengamatan Jonathan & Machdar (2018) mengungkapkan bahwa earning quality yang bagus sejalan dengan informasi laba yang bagus juga yang akan menjadi magnet bagi investor untuk berinvestasi.…”
Section: Kualitas Laba Financial Leverage Dan Reaksi Pasar Berpemgaru...unclassified
“…Earnings management carried out by managers in managing company profits aims to improve the company's financial performance (Mahrani & Soewarno, 2018). As evidenced by the research of Utami et al (2019), earnings management affects banking financial performance. Banking performance will decline if the company performs earnings management in the form of inaccurate financial reporting.…”
Section: Earning Management Toward Financial Performancementioning
confidence: 99%